Geographical heterogeneity in prevalence of subclinical malaria infections at sentinel endemic sites of Myanmar - Ziling Liu; Than Naing Soe; Yan Zhao; Aye Than; Cho Cho; Pyae Linn Aung; Yuling Li; Lin Wang; Huilin Yang; Xiangnan Li; Danni Li; Zhiping Peng; et al. (Parasites & Vectors, 2019)
Abstract Background The malaria burden of Myanmar still remains high within the Greater Mekong Subregion of Southeast Asia. An important indicator of progress towards malaria elimination is the prevalence of parasite infections in endemic populations. Information about malaria epidemiology is mostly derived from reports of confirmed acute malaria cases through passive case detection, whereas the prevalence of baseline subclinical malaria infections is much less known. Methods In this study, cross-sectional surveys were conducted during the rainy season of 2017 in four townships (Bilin, Thabeikkyin, Banmauk and Paletwa) of Myanmar with divergent annual malaria incidences. A total of 1991 volunteers were recruited from local villages and Plasmodium subclinical infections were estimated by light microscopy (LM), rapid diagnostic tests (RDTs) and nested PCR. The nested PCR analysis was performed with a modified pooling strategy that was optimized based on an initial estimate the infection prevalence. Results The overall malaria infection prevalence based on all methods was 13.9% (277/1991) and it differed drastically among the townships, with Paletwa in the western border having the highest infection rate (22.9%) and Thabeikkyin in central Myanmar having the lowest (3.9%). As expected, nested PCR was the most sensitive and identified 226 (11.4%) individuals with parasite infections. Among the parasite species, Plasmodium vivax was the most prevalent in all locations, while Plasmodium falciparum also accounted for 32% of infections in the western township Paletwa. Two RDTs based on the detection of the hrp2 antigen detected a total of 103 P. falciparum infections, and the ultrasensitive RDT detected 20% more P. falciparum infections than the conventional RDT. In contrast, LM missed the majority of the subclinical infections and only identified 14 Plasmodium infections. Conclusions Cross-sectional surveys identified considerable levels of asymptomatic Plasmodium infections in endemic populations of Myanmar with P. vivax becoming the predominant parasite species. Geographical heterogeneity of subclinical infections calls for active surveillance of parasite infections in endemic areas. The pooling scheme designed for nested PCR analysis offers a more practical strategy for large-scale epidemiological studies of parasite prevalence. Such information is important for decision-makers to put forward a more realistic action plan for malaria elimination.